ZD 7288, an HCN channel blocker, attenuates chronic visceral pain in irritable bowel syndrome-like rats - Chen, Yu (Baishideng Publishing Group Co., Limited, 2014)
AIM: To investigate the effects of ZD 7288, a hyperpolarization-activated cyclic nucleotide-gated (HCN) channel blocker, on rats with chronic visceral pain. METHODS: Rats with visceral hypersensitivity were generated using neonatal colon irritation during postnatal days 8-15 as described previously. Visceral hypersensitivity was evaluated using electromyographic (EMG) responses of abdominal external oblique muscles to 20-80 mmHg colorectal distentions (CRD). Abdominal withdrawal reflex (AWR) scores and pain thresholds were also detected in adult rats. Different doses of ZD 7288 (25, 50, and 100 nmol/L) were intrathecally administered in rats to study the role of spinal HCN channel in chronic visceral hypersensitivity. RESULTS: EMG responses to 20-80 mmHg CRD and AWR scores under 20-60 mmHg CRD significantly increased in rats with visceral hypersensitivity compared to control rats (P < 0.05). The pain threshold in rats with visceral hypersensitivity significantly decreased compared to control rats (P < 0.05). Treatment with 50-100 nmol/L ZD 7288 significantly inhibited EMG responses (16%-62%, 80-20 mmHg CRD, P < 0.05) and AWR scores (24%-37%, 40-20 mmHg CRD, P < 0.05; 12%-61%, 80-20 mmHg CRD, P < 0.05, respectively), and significantly increased pain thresholds (32%-77%, P < 0.05). CONCLUSION: Spinal HCN channels may play an important role in chronic visceral hypersensitivity.